Results of combined vascular reconstruction by means of AV loops and free flap transfer in patients with soft tissue defects - Meyer, Alexander; Horch, Raymund E.; Schöngart, Elisabeth; Beier, Justus; Taeger, Christian; Arkudas, Andreas; Lang, Werner (Journal of Plastic Reconstructive and Aesthetic Surgery, 2016)
Free flap transplantation to vascular reconstructions as arteriovenous (AV) loops has been established in centers as a feasible therapeutic option for defect reconstruction in the absence of proper recipient vessels, caused by oncologic resections, radiation, or trauma. We report our 10-year experience in free flap transplantation after vascular reconstruction with special emphasis on complication rate and postoperative mobility.Forty-seven patients (mean age: 60 years, range: 19-86) were included. Defect etiology was posttraumatic in 19 patients; 14 defects were due to oncological resections and seven sternal osteomyelitis; three patients presented with radiation ulcers, two with aseptic femoral head necrosis, and one with defects caused by acne inversa and hip joint prosthesis infection. Long-term follow-up was 45 months (range: 0-126). We performed arterial revascularization with 36 AV loops, eight bypass grafts, and three venous interposition grafts. Subsequent tissue transfer comprised 24 latissimus dorsi, two vastus lateralis, one gracilis, one anterior lateral thigh (ALT), 16 rectus abdominis, one radialis forearm, and two osteocutaneous vascularized fibula flaps.Complications occurred in 25/47 patients (53%). Early complications included five acute occlusions of arterial reconstructions and six major bleedings. There were six flap losses and three major amputations. Two in-hospital deaths were observed (4%). Overall survival accounted for 89.0 and 74.7% after 1 and 5 years, respectively.The 5-year survival rate in long-term follow-up is favorable, despite an initially elevated complication rate. Successful defect coverage can be achieved by this method in a high percentage of patients.
EVALuna2:15223